Synthesis, Antibacterial and Antifungal Evlaution of Novel Pyrazoline Derivatives (Dhaka University Journal of Pharmaceutical Sciences, 2018)
A new series of chalcones (2a-j) were prepared by reacting substituted aldehydes and substituted ketones in alcohol medium in presence of NaOH. The chalcones underwent selective cyclization with guanicol hydrazide (1) in glacial acetic acid medium to yield the title compounds 1,3,5-trisubstituted pyrazolines (3a-j). The new compounds were characterized on the basis of 1H-NMR, IR and mass spectral data. All the newly synthesized compounds were evaluated for their in-vitro antibacterial and antifungal activities. Some of the tested compounds 3a and 3e showed good activity against bacterial strains and compounds 3d and 3h revealed good activity against fungal strains.Dhaka Univ. J. Pharm. Sci. 17(2): 221-226, 2018 (December)